Rancang Bangun Sistem Informasi Akademik Menggunakan Framework Laravel 11 (Studi Kasus : SMKN 1 Palasah) - Ahmad, Aang Ibnu; Suhendri, Suhendri (Universitas Majalengka, 2025)
The rapid development of information technology has significantly impacted the education sector, particularly in the management of academic data. Manual data processing often leads to delays, errors, and inefficiencies in academic services. This study aims to design and develop a web-based Academic Information System using the Laravel 11 framework at SMKN 1 Palasah. The research was conducted by applying the System Development Life Cycle (SDLC) methodology, which includes stages of requirement analysis, system design using Unified Modeling Language (UML), implementation, and system testing. The proposed system integrates features such as student and teacher data management, subject scheduling, attendance, assessments, online examinations, and discussion forums. The system was tested using the black box testing method to ensure functionality and reliability. The results show that the developed system successfully improves the efficiency of academic data management, minimizes errors caused by manual processes, and provides a secure and structured platform for academic services. This system is expected to support digital transformation and enhance the quality of education services in schools.